STEM Quartet to Improve Creative Thinking Skills (CreaTS) for High School Students in Physics Learning - Julia Maysarah Rosha; Arif Hidayat; Andi Suhandi (Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to improve high school students' creative thinking skills (CreaTS) in physics learning by applying the STEM Quartet. This study used an experimental design with the pre-experimental method, and the design used was a one-group pretest-posttest design. The population in this study were all students of class X at a high school in Bandung. The sampling technique in this study was purposive. The sample for this research is 16 students aged 15 to 16 years. The instrument in this study was the CreaTSIT (Creative Thinking Skill Instrument Test) in the form of an essay consisting of 20 items. Data were analyzed using the gain score, Wilcoxon signed rank test, stacking, and racking. The results showed a significant difference between the pretest and posttest scores with a p-value of 0.00 and an increase in creative thinking skills (CreaTS) in each indicator with an N-Gain value of 0.67 in the medium category. The four aspects of creation experienced increases, changes in the difficulty level of items, and changes in students' creative thinking skills, as shown through stacking and racking analysis. This study suggests that applying the STEM Quartet can be used as an alternative to improve students' creative thinking skills (creaTS) and can contribute to the world of Indonesian education, especially for physics teachers and physics education researchers.